Networks of interpretation: An ethnography of the quest for IFRS consistency in a global accounting firm - Kohler, Hervé; Pochet, Christine; Gendron, Yves (Accounting, Organizations and Society, 2021)
Because of their complexity and principle-based nature, the creation of International Financial Reporting Standards (IFRS) engendered significant uncertainty that modified the order of things within large accounting firms. This motivated them to establish Professional Practice Function (PPF) units to try to ensure a credible degree of consistency in applying IFRS across a wide range of financial reports at the international level. We study backstage dynamics surrounding a PPF national unit in one of the Big Four firms. We focus on the rise of the PPF as an expert-based control device within the firm, and the role PPF members play as knowledge brokers to interpret IFRS. Our investigation is carried out through ethnographic fieldwork supplemented by interviews with PPF members and field auditors. The analysis brings forward some of the organizational dynamics surrounding PPF members' efforts to establish their credibility as intermediaries both hierarchically, between administrative partners and field auditors, and epistemically, between the unifying logic of IFRS and auditees' financial reporting specifics. Ultimately, our analysis points to the role of the PPF as a gatekeeping or internal control device that mediates between different pools of knowledge to monitor the firm's reputation risk against IFRS implementation challenges. From a legal perspective, our ethnography documents how accounting “law” is made at the firm level and how PPF members strive for consistency – in spite of significant epistemological and organizational challenges. Our ethnography also shows that complex IFRS interpretation issues are not resolved through one person's judgment; instead, the firm's structure surrounding the PPF allows for the constitution of inter-individual judgment that transcends national, sectoral, and (sometimes) organizational boundaries. Finally, we see one important contribution of our work as helping reveal the limits of large conceptual categories such as “auditors”, which tend to downplay the dynamics of convoluted practice relationships.